Estado nutricional y su relación con la calidad de vida en pacientes adultos con insuficiencia renal crónica de la Unidad de Hemodiálisis Dial-Ríos del Cantón Vinces, octubre 2019 - marzo 2020. - Aspiazu García, Jenny Yamilex (2020)
This research work was carried out in the DIAL-RÍOS Hemodialysis Unit in the city of Vinces which is responsible for providing specialized medical care in patients with renal insufficiency. The objective of this research is to establish a relationship between the nutritional status and quality of life of patients with CRF because this disease progressively affects the functionality of the kidneys to cause death, so why, This research is based on the evaluation of the nutritional status of each one of them, it is possible to establish control parameters that allow improving their health conditions and fighting the disease in the best possible way. The research methodology used in this research work was under the qualitative-quantitative approaches because numerical data and fundamental aspects of the subject studied were collected, in the same way the types, methods, techniques and research instruments aimed at the beneficiaries were applied. of this study to collect the necessary information of the variables under analysis such as nutritional status and its relationship with the quality of life of patients with chronic renal failure. This research resulted in the majority of those diagnosed with chronic renal failure being male and that many of them are of limited economic resources, also 51% of them have low weight, this due to the degenerative characteristics of this disease. In conclusion, chronic renal failure is a high-risk disease that initially has no symptoms and can cause death of people but is not diagnosed in time, for this reason it is necessary to establish a nutritional guide that allows adequate nutritional status and that in this way the quality and living conditions of these people with CRI are improved.